Pengaruh Kepercayaan dan Hambatan Berpindah Terhadap Loyalitas (Studi Pada Pelanggan Produk Skincare Garnier di Majalengka Kota) (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2021)
Competitive competition in the business world is getting tighter, making thecompany have to be able to determine the right strategy for the sustainability of thecompany, namely by being able to market its products according to the wishes andexpectations of consumers / customers. There are many factors that consumers /customers consider to be loyal to a product, including trust and barriers tochange.The purpose of this study was conducted to determine the partial effect of truston loyalty and barriers to movement on loyalty.The method in this research uses descriptive and verification research methods.The population in this study were customers of Garnier Skincare Products inMajalengka city, which includes the areas of MajalengkaWetan and MajalengkaKulonVillages. The sample in this study amounted to 100 people using purposive samplingtechnique. The data collection technique is done by distributing questionnaires.Testing of data instruments was done by testing the validity and reliability testing.While the data analysis is the classical assumption test, multiple regression analysis,determination coefficient analysis, and hypothesis testing.Based on the results of the study, it shows that trust and barrier to moveis in thehigh category. Trust has a positive and significant effect on loyalty. Barriers toswitching have a positive and significant effect on loyalty.